The divergence between actual central banking and conventional economics - Sławiński, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
Actual money creation and the conduct of monetary policy are in some respects at variance with what is assumed in mainstream economics. Nonetheless, in turbulent times central banks have tended to take decisions that followed the widely accepted best practice. The resulting consequences were very unfortunate on at least two occasions. In the early 1930s, the dominant liquidationist doctrine prevented the Federal Reserve from providing commercial banks with adequate liquidity to stop runs by depositors. In the 2000s, the belief that stable inflation is sufficient to keep the economy on an equilibrium growth path prevented central banks from hiking interest rates enough to stop unsustainable lending booms. In both cases the central banks’ decisions were not questioned as they were in line with the prevailing beliefs of the day. Both experiences call for highlighting the divergences between how central banks are assumed to operate in mainstream economics and how they operate in practice. Identifying these divergences should improve the democratic accountability of central banks and provide inspiration for new advances in research
Argumenta Oeconomica, 2019, Nr 1 (42), s. 5-20
Keywords: money creation; monetary policy